2009
DOI: 10.24972/ijts.2009.28.1.68
|View full text |Cite
|
Sign up to set email alerts
|

A Viable Model and Self-Report Measure of Spiritual Intelligence

Abstract: A four-factor model of spiritual intelligence is first proposed. Supportive evidence is reviewed for the capacities of critical existential thinking, personal meaning production, transcendental awareness, and conscious state expansion. Based on this model, a 24-item self-report measure was developed and modified across two consecutive studies (N = 619 and N = 304, respectively). The final version of the scale, the Spiritual Intelligence Self-Report Inventory (SISRI-24), displayed excellent internal reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
2
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 61 publications
6
179
2
18
Order By: Relevance
“…Section Two captured SI, and the scale with 24 items developed by King and DeCicco (2009) [Spiritual Intelligence Self-Report Inventory (SISRI)] was adopted in this study. Section Three captured caring behaviors of nurses, and the scale with 24 items developed by Wu et al (2006) was adopted in this research.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Section Two captured SI, and the scale with 24 items developed by King and DeCicco (2009) [Spiritual Intelligence Self-Report Inventory (SISRI)] was adopted in this study. Section Three captured caring behaviors of nurses, and the scale with 24 items developed by Wu et al (2006) was adopted in this research.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, some authors have asserted that SI influences EI (Hosseini et Zohar & Marshall, 2000). The four dimensions of SI (King & DeCicco, 2009) are: (i) critical existential thinking (CET), (ii) personal meaning production (PMP), (iii) transcendental awareness (TA), and (iv) conscious state expansion (CSE). The four dimensions of EI (Schutte et al, 1998) are: (i) perception of emotion (PE), (ii) managing one's own emotions (ME), (iii) managing other's emotions (MOE), and (iv) utilization of emotion (UE).…”
Section: Si and Eimentioning
confidence: 99%
See 1 more Smart Citation
“…King and DeCicco (2009) extensively reviewed previous SI models, conducted empirical studies, and developed the SISRI-24, which they reported to have good internal reliability and external validity. The SISRI is a 24-item self-report scale that consists of four subscales: CET, PMP, TA, and CSE (12). Antunes et al calculated internal reliability of the full scale as estimated by Cronbach's alpha of 0.92, and the four subscales Cronbach's alpha ranged from 0.78 to 0.91, which indicates that the SISRI-24 had good reliability (27) questionnaire, content validity by 12 experts was used and CVR of 0.83 and CVI of 0.81 was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…King and DeCicco (2009) conducted empirical studies to investigate the factor structure of SI and identified four core components: (a) critical existential thinking (CET), which refers to thinking about the essence of reality, the world, and other existential and non-existential concerns in relation to oneself; (b) personal meaning production (PMP), which refers to finding personal meaning in all experiences and mastering the purpose of one's life (12), and necessary component of SI (13); (c) transcendental awareness (TA), which refers to identifying the means of achieving transcendence from oneself and the physical world; and (d) conscious state expansion (CSE), which refers to the ability to control how and when to enter higher states of consciousness (12). The findings of King and DeCicco also supported the notion that CET is a kind of spiritual ability, that SI consists of a set (14).…”
Section: Introductionmentioning
confidence: 99%